Maliwawa figures—a previously undescribed Arnhem Land rock art style. Issue 3 (1st September 2020) - Taçon, Paul S.C.; May, Sally K.; Lamilami, Ronald; McKeague, Fiona; Johnston, Iain G.; Jalandoni, Andrea; Wesley, Daryl; Sanz, Ines Domingo; Brady, Liam M.; Wright, Duncan; Goldhahn, Joakim
Abstract: In this paper, a previously undescribed rock art style consisting of large human figures and animals with stroke-line infill is introduced. These depictions have been named Maliwawa Figures. They are primarily found in northwest Arnhem Land and to date have been recorded at 87 sites from Awunbarna (Mount Borradaile area) to the Namunidjbuk clan state of the Wellington Range. There are solitary figures and others arranged in compositions or scenes. We describe the features of this style, its distribution, subject matter and probable age. The results of a detailed analysis of all sites are discussed and a new, refined Arnhem Land rock art chronology is presented. It is concluded that Maliwawa Figures are most likely to date between 6, 000 to 9, 400 years of age and to be contemporaneous with Northern Running Figures and Yam Figures found at sites to the south.